THE ROLE OF AESTHETIC CULTURE IN THE FORMATION OF THE WORLDVIEW OF FUTURE MEDICAL PROFESSIONALS (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
This article explores the importance of aesthetic culture in the development of the worldview and professional identity of future medical professionals. It emphasizes the role of aesthetic values in shaping emotional resilience, ethical conduct, and humanistic qualities in healthcare workers. In the context of New Uzbekistan, where educational and cultural reforms are a national priority, the integration of aesthetic education into the training of medical students is vital for producing well-rounded, compassionate, and culturally aware physicians.